Pemberdayaan Masyarakat Bidang Pendidikan, Kewirausahaan, dan Lingkungan di Kampung Parumasan Kota Serang: Community Empowerment on Education, Entrepreneurship and Environment Issues at Parumasan Village, Serang City - Aulia, Rida; Kusumastuti, Retno (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
Kampung Parumasan of Serang City, Banten province of Indonesia, is a centre of Kerupuk Bawang production as a substitute for Emping chips when melinjo (Gnetum gnemon), the emping material, are not available. However, humble packaging and ineffective online marketing strategies are becoming a problem for them. Besides, waste disposal of used frying oil is also feared to interfere with the environment. Furthermore, the kampung also does not have a public library or park for children so they are becoming overwhelmed with their gadgets. Therefore, three interesting issues of Kampung Parumasan then became the fundamental idea for the community empowerment team of Universitas Indonesia. Carried out from September to November 2021 every Saturdays and Sundays, by focusing on entrepreneurship, education, and environment issues, the purpose of the program is to increase public knowledge through product packaging and marketing training, children's reading interest through reading park activities, and socializing the movement of growing vegetables and trees in the kampung area. Kampung Parumasan Kota Serang, Provinsi Banten, Indonesia, merupakan sentra produksi Kerupuk Bawang sebagai pengganti emping ketika bahan emping melinjo (Gnetum gnemon) tidak tersedia. Namun, kemasan yang sederhana dan strategi pemasaran online yang tidak efektif menjadi masalah bagi mereka. Selain itu, pembuangan limbah minyak goreng bekas juga dikhawatirkan akan mengganggu lingkungan. Apalagi kampung ini juga tidak memiliki perpustakaan umum atau taman untuk anak-anak sehingga mereka kewalahan dengan gadget mereka. Oleh karena itu, tiga isu menarik dari Kampung Parumasan tersebut kemudian menjadi gagasan mendasar bagi tim pemberdayaan masyarakat Universitas Indonesia. Diselenggarakan pada bulan September s/d November 2021 setiap hari Sabtu dan Minggu, dengan fokus pada isu kewirausahaan, pendidikan, dan lingkungan, program ini bertujuan untuk meningkatkan pengetahuan masyarakat melalui pelatihan pengemasan dan pemasaran produk, minat baca anak melalui kegiatan taman bacaan, dan sosialisasi. pergerakan menanam sayuran dan pohon di kawasan kampung.